2017
DOI: 10.1007/s00181-017-1335-1
|View full text |Cite
|
Sign up to set email alerts
|

The dollar–euro exchange rate and monetary fundamentals

Abstract: This study analyses the relationship between the dollar-euro exchange rate and macroeconomic fundamentals according to the monetary model after 1999. Multivariate and time-varying univariate cointegration techniques are used to test for a long-run equilibrium and changes in the underlying coefficients. Our results provide clear evidence of a long-run relationship between exchange rates and fundamentals. However, we find significant changes in the economic impact of fundamentals on the dollar-euro exchange rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 54 publications
(53 reference statements)
0
3
0
Order By: Relevance
“…Another direction for future research on international markets is testing for market inefficiencies causing carry trade profitability in foreign exchange (the carry trade strategy is discussed in [76], chap.7). The time-varying coefficient methodology that we investigate should also play a part in this research along the lines of [77]. Another possible avenue would be to consider nonlinear models either with a business cycle transition variable or more generally, a smooth transition approach such as the STAR or Markov regime-switching models also accounting for measurement/specification errors or endogeneity biases.…”
Section: Resultsmentioning
confidence: 99%
“…Another direction for future research on international markets is testing for market inefficiencies causing carry trade profitability in foreign exchange (the carry trade strategy is discussed in [76], chap.7). The time-varying coefficient methodology that we investigate should also play a part in this research along the lines of [77]. Another possible avenue would be to consider nonlinear models either with a business cycle transition variable or more generally, a smooth transition approach such as the STAR or Markov regime-switching models also accounting for measurement/specification errors or endogeneity biases.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have demonstrated the time-varying relationship between exchange rates and macroeconomic fundamentals (Frömmel et al, 2005;Junttila & Korhonen, 2011;Yuan 2011;Wu, 2015;Beckmann et al, 2018). MS models define different states of regimes and allow us to analyze the asymmetric behaviors of variables conditional on the regimes (Baharumshah et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In order to overcome modelling limitations, the Markov switching model allows regressors to switch between states or regimes to estimate individual regime coefficients [22,23]. Compared with other ways of modelling time-varying coefficients, such as state-space models (see, e.g., [24]), the Markov switching model is superior in the case when nonlinearities are caused by exogenous events [22].…”
Section: Introductionmentioning
confidence: 99%